MANAGEMENT AND DIAGNOSTIC RESEARCH FOR PATIENTS WITH LOW BLOOD FERRITIN AND MAXILLOFACIAL AREA PHLEGMON - Kambarova Shakhnoza Alikhuseinovna (Web of Journals Publishing, 2024)
Low iron levels in bone marrow and blood plasma cause reduced hemoglobin synthesis, which hinders the trophic development of organs and tissues. This condition is known as iron deficiency anemia.
Keywords: Blood plasma, medicinal plant, iron substance, hemoglobin, pus, tooth, odontogen.